Dirt and Debt: The Racialization of Default in Brazil - Millar, Kathleen (Anthropologica, 2024)
Beginning in the early 2000s, policies and legislation aimed at financial inclusion drew millions of low-income Brazilians into the banking system for the first time. When many of these consumers were unable to keep up with credit card payments, they acquired a “dirty name”—the common expression in Brazil for default. An analysis of the historical origins and current use of this expression shows how it operates as a technology of racialization that legitimates forms of expropriation under financial capitalism. Drawing upon longstanding associations between Blackness and dirt in Brazil, the expression “dirty name” naturalizes inequalities while erasing alternative financial practices and relations in Brazil’s urban peripheries.